Solid‐State Electrolyte‐Gated Graphene in Optical Modulators. Issue 19 (15th March 2017) - Rodriguez, Francisco J.; Aznakayeva, Diana E.; Marshall, Owen P.; Kravets, Vasyl G.; Grigorenko, Alexander N.
Abstract : The gate‐tunable wide‐band absorption of graphene makes it suitable for light modulation from terahertz to visible light. The realization of graphene‐based modulators, however, faces challenges connected with graphene's low absorption and the high electric fields necessary to change graphene's optical conductivity. Here, a solid‐state supercapacitor effect with the high‐ k dielectric hafnium oxide is demonstrated that allows modulation from the near‐infrared to shorter wavelengths close to the visible spectrum with remarkably low voltages (≈3 V). The electroabsorption modulators are based on a Fabry–Perot‐resonator geometry that allows modulation depths over 30% for free‐space beams. Abstract : A solid‐state supercapacitor effect found in graphene/hafnium oxide devices is used to gate graphene and obtain optical modulation from near‐infrared to visible wavelengths with small voltages. The electroabsorption modulators are based on a Fabry–Perot resonator working for free‐space beams in transmission or reflection.